2012
DOI: 10.1038/ajh.2012.63
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Reproducibility of Noninvasive 24-h Ambulatory Aortic Blood Pressure Monitoring With a Brachial Cuff-Based Oscillometric Device

Abstract: In conclusion, these data suggest that noninvasive 24-h ABPM is feasible and provides reproducible values. Future studies should validate the prognostic ability of 24-h aortic hemodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 26 publications
4
56
0
8
Order By: Relevance
“…Previous validation studies in hypertensive and healthy volunteers showed acceptable agreement between Mobil-O-Graph-derived variables and invasive and noninvasive measurements (24,(28)(29)(30). In a validation study in hemodialysis patients, Mobil-O-Graph provided estimates of aortic SBP, AIx, and PWV similar to those obtained by SphygmoCor (ArtCor, Sydney, Australia) (31), the most widely applied method for noninvasive assessment of these measures.…”
Section: Abpm With Mobil-o-graph Devicementioning
confidence: 57%
“…Previous validation studies in hypertensive and healthy volunteers showed acceptable agreement between Mobil-O-Graph-derived variables and invasive and noninvasive measurements (24,(28)(29)(30). In a validation study in hemodialysis patients, Mobil-O-Graph provided estimates of aortic SBP, AIx, and PWV similar to those obtained by SphygmoCor (ArtCor, Sydney, Australia) (31), the most widely applied method for noninvasive assessment of these measures.…”
Section: Abpm With Mobil-o-graph Devicementioning
confidence: 57%
“…Previous validation studies in hypertensive and healthy volunteers showed acceptable agreement between Mobil-O-Graph-derived parameters and invasive and noninvasive measurements. 20,[22][23][24] In hemodialysis patients, Mobil-O-Graph provided comparable estimates of office aortic SBP, AIx, and PWV with that obtained by Sphygmocor (ArtCor, Sydney, Australia), which is the most widely applied method for noninvasive assessment of these parameters. 14 …”
Section: Study Procedures and Ambulatory Bp Monitoringmentioning
confidence: 94%
“…The "gold standard" method for evaluation of PWV is the measurement of cf-PWV [15]. In this study, PWV was measured by the device Mobil-O-Graph and calculated by complex mathematical estimation, which could be a focus for criticism, although validation was proved in several studies [23,[32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The device uses the integrated ARCSolver algorithms (Austrian Institute of Technology, Vienna, Austria) to derive aortic stiffness surrogates based on brachial BP readings by a generalized transfer function [31,32]. Previous studies have proven the validity of the Mobil-O-Graph for BP monitoring and pulse wave analysis against established invasive and noninvasive techniques in various populations, including hemodialysis patients [23,[32][33][34][35]. The measurements were taken of the non-fistula arm with circumference-adapted arm cuffs and started before the midweek dialysis session independent of the dialysis shift.…”
Section: Data Collection and Measurementsmentioning
confidence: 99%